A very high speed FPGA-based Sudoku solver - AlDahoul, Nouar; Htike@Muhammad Yusof, Zaw Zaw; Zarzar, Mouayad (2015)
This paper proposes FPGA (Field Programmable Gate Array) based high speed Sudoku solver platform. It focuses on the FPGA ability to solve complex problems in a little time. This ability comes from parallel execution of multiple processes at the same time. FPGA with 50 Mega Hertz crystal is used. The output of this work is an embedded system that is able to solve hard 9×9 puzzles within 1 µs. Some terminals such as PS2 mouse and VGA monitor were used to provide an interactive interface between the user and the platform.